A grave mistake - Cameron, Stella (Chatswood, New South Wales : Mira, 2006)
Dead: one ordinary man. Just the latest in a string of losers in the wrong place at the worst time. Not the kind of case to yank New Orleans homicide detective Guy Gautreaux back from his leave of absence in Toussaint, Louisiana. There's someone in Toussaint Guy will do anything to protect. Jilly Gable is desperate to find the love of the family who abandoned her as a child. And when the wife of a powerful New Orleans antiques dealer and loan shark sweeps into town claiming to be her mother, Jilly is all too willing to love and forget. Slowly and methodically, evil closes in on Jilly, and only the truth--and Guy--can save her. Connecting the dots between the Big Easy and Toussaint all but cinches his case, but Jilly and Guy are still in danger. They have only each other for protection.
Keywords: Police -- Louisiana -- New Orleans -- Fiction; Thrillers (Fiction)